1996
DOI: 10.1016/s0960-9822(96)00749-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-kinase signals activate a selective subset of Rac/Rho-dependent effector pathways

Abstract: Our results demonstrate that PI 3-kinase induces a selective subset of cellular responses, but is not sufficient to stimulate the full repertoire of Rac- or Rho-mediated responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
215
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 254 publications
(231 citation statements)
references
References 57 publications
15
215
0
1
Order By: Relevance
“…In this context, PTEN induced T lymphomas are invasive tumors that originate in the thymus but cause morbidity when they disseminate to the periphery and extensively infiltrate multiple tissues including the spleen, liver, kidney, and bone marrow (Suzuki et al, 2001;Hagenbeek et al, 2004). The previous idea of how PTEN might control cell adhesion and motility is that PI(3,4,5)P 3 signaling regulates the GTPases Rac and RhoA and coordinates actin and microtubule dynamics (Reif et al, 1996;Liliental et al, 2000). PTEN also has protein phosphatase activity that inhibits cell motility (Raftopoulou et al, 2004;Leslie et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, PTEN induced T lymphomas are invasive tumors that originate in the thymus but cause morbidity when they disseminate to the periphery and extensively infiltrate multiple tissues including the spleen, liver, kidney, and bone marrow (Suzuki et al, 2001;Hagenbeek et al, 2004). The previous idea of how PTEN might control cell adhesion and motility is that PI(3,4,5)P 3 signaling regulates the GTPases Rac and RhoA and coordinates actin and microtubule dynamics (Reif et al, 1996;Liliental et al, 2000). PTEN also has protein phosphatase activity that inhibits cell motility (Raftopoulou et al, 2004;Leslie et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors such as EGF have been shown to activate the JNK pathway through PI3K (Logan et al, 1997). Overexpression of PI3K catalytic subunit (p110) can lead to Rac activation (Klippel et al, 1996;Minden et al, 1995;Minden and Karin, 1997) and its expression in COS cells was shown to induce activation of JNK (Rei et al, 1996). Taken together these data suggest that the PI3K activated pathway could be similarly involved in coupling Rac signalling to stress activated kinases.…”
Section: Introductionmentioning
confidence: 86%
“…Increased production of D-3 phosphoinositides by PI3K contributes to an integrin-mediated pathway activating Rac to promote cell spreading (13,50,51,55), and both PI3K and PLC-␥1 have been implicated as major effector molecules promoting cell motility following activation of receptor protein-tyrosine kinases (12,35). Finally, Src phosphorylation of FAK itself, in addition to promoting focal adhesion turnover through FAK degradation as discussed above, could also conceivably stimulate cell migration through FAK Tyr-925 phosphorylation.…”
Section: F397-fakmentioning
confidence: 98%